1972
DOI: 10.1177/000992287201101011
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Hypervitaminosis A with Intracranial Hypertension and Low Cerebrospinal Fluid Concentration of Protein

Abstract: An unusually high dietary intake can lead to vitamin A intoxication. These two children had clinical and radiologic evidences of increased intracranial pressure and low cerebrospinal fluid protein concentrations. &dquo;... it made us rzlt sicke, specially three that were exceeding sicke, czrzcl we verily thought we should have lost them all, for all their skins came of from the foote to the head; but yet they recoitred again, fou zz~hich we gave Cod heartie thanks.&dquo; GERRIT DE VEER, 3 historian of an Arcti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

1975
1975
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 9 publications
1
8
0
1
Order By: Relevance
“…The rate of appearance Cerebrospinal fluid absorption in primary hypoparathyroidism has been established in normal subjects by Abbott and Alksne (1968) who found plasma values 24 hours after injection ranging from 41 to 60% (mean 48%) of the total cisternal dose. These values are similar to those obtained in dogs where the plasma level of 131I RISA increases steadily to a point of equilibrium 16 to 24 hours after injection (van Wart et al, 1960;Abbott and Alksne, 1968). In the patient studied, only 16% of the cisternally injected 1311 RISA had appeared in the plasma after 20 hours and equilibrium was not achieved until 72 hours.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The rate of appearance Cerebrospinal fluid absorption in primary hypoparathyroidism has been established in normal subjects by Abbott and Alksne (1968) who found plasma values 24 hours after injection ranging from 41 to 60% (mean 48%) of the total cisternal dose. These values are similar to those obtained in dogs where the plasma level of 131I RISA increases steadily to a point of equilibrium 16 to 24 hours after injection (van Wart et al, 1960;Abbott and Alksne, 1968). In the patient studied, only 16% of the cisternally injected 1311 RISA had appeared in the plasma after 20 hours and equilibrium was not achieved until 72 hours.…”
Section: Discussionsupporting
confidence: 88%
“…Nine months after correction of his serum calcium the rate of appearance had increased to 53% with equilibrium at 20 hours. It has been suggested that the CSF volume is increased in patients with benign intracranial hypertension (Davidoff, 1956;Greer, 1968;Siegel and Spackman, 1972) but in this patient computed tomography did not show any detectable change in the ventricular size or prominence of the subarachnoid spaces after treatment. Whilc this does not rule out smaller changes in the size of the basal subarachnoid cisterns it certainly indicates that any change in volume was small and could not account for the marked increase in the rate of appearance of 1311 RISA in the plasma.…”
Section: Discussionmentioning
confidence: 53%
“…Multiple case reports found benign intracranial hypertension, or pseudotumor cerebri, characterized by headache, papilledema, and normal CT/MRI and CSF, in children and adults exposed to high levels of vitamin A (Alemayehu 1995;Gerber et al 1954;Gomber and Chellani 1996;Lombaert and Carton 1976;Marie and See 1954;Oliver and Havener 1958;Seigel and Spackman 1972;Selhorst et al 1984;Spector and Carlisle 1984). Selhorst (Selhorst et al 1984) reported that 5/50 patients with "idiopathic" pseudotumor cerebri were found by dietary history to be ingesting large amounts of Vitamin A in their diet.…”
Section: Class Effect: Neuropsychiatric Effects Of Vitamin Amentioning
confidence: 99%
“…Increased intracranial pressure and splitting of the sutures has also been reported [4]. Radiographically, the most common manifestation is ulnar periostitis.…”
Section: Discussionmentioning
confidence: 95%